Sustainable Consumption in the Islamic Economy: A Comparative Analytical Study - Hassan, Diaa (The Arab Journal of Administration, 2022)
The study aimed to identify the concept of sustainable consumption and its dimensions, and to reveal the extent of sustainable consumption in the Islamic economy. To achieve this, the study adopted the comparative analytical method. By reviewing the concept of sustainable consumption formulated by international organizations and specialized literature, and deducing the elements of sustainability in them, then reviewing the controls of consumption in the Islamic economy; Through the Noble Qur’an, the Noble Sunnah, books of Islamic heritage, and contemporary economic thought, analyzing them and deducing the elements of sustainability in them. In this, the study reached a number of results, the most important of which was that consumption in the Islamic economy is by its nature sustainable, and that the Islamic economy has the lead and leadership in paying attention to consumption and making sure that it is “moderate” that does not have negative effects on the individual, society or nature. The study revealed the sustainability of consumption in the Islamic economy, and recommended the necessity of adopting consumption controls in the Islamic economy as a basis for sustaining consumption and achieving sustainable development, and to reduce the risks that threaten life on the planet.